KARAKTERISTIK PENYEBAB TERJADINYA DEPRESI POSTPARTUM PADA PRIMIPARA DAN MULTIPARA - Prima Daniyati Kusuma (Jurnal Keperawatan Notokusumo, 2017)
Background: Getting pregnant, delivering baby and becoming a mother were physiologic conditions. Some postpartum women could adapt role changes as mother and some others couldn’t adapt, resulted in stress condition that, if it was continue, became postpartum depression. The lightest form of postpartum depression usually unrecognized because it presumed to be normal. Primiparous motherhood and multiparous mother during the postpartum period may experience a very wide range of emotional response disorders, depression is the most common feature of receiving the baby's presence. Many women, especially multiparas who experience feelings of disappointment after childbirth are associated with the great experience of childbirth and in primiparous moms doubt the ability to address the need to raise children effectively. Objective: To determine the difference in causes of postpartum depression events in primiparous and multiparous. Method: Analytical survey research using cross sectional research method. Result: . The incidence of postpartum depression was greater in the primiparous mother group of 24 people (70.59%) than the multiparous mother group of 20 people (58.82%). There is no relationship between age, education level, and maternal delivery with postpartum depression. There is a relationship between employment and maternal marital status with postpartum depression Conclusion: Obtained a value of 0.310, sig value> 0.05, it can be concluded, there is no significant difference between primiparous variables with multiparous in the incidence of postpartum depression.